Law Enforcement of Criminal Acts in the Fisheries Sector (Study of Ships Sailing Without Permission) - Nuriyanti Nuriyanti; Indanna Zulfa Nadia Hidayat; Apriyani Purnamasari; Endang Sutrisno; Mohamad Sigit Gunawan (Pusat Publikasi Nusantara, 2025)
The role and responsibility of fishing vessel captains in Indonesia, especially regarding the obligation to have a Sailing License (SPB) as a legal requirement to be able to sail. The captain as the main worker of the ship owner has a great responsibility in maintaining the safety of the ship, cargo, and crew. The SPB Ordinance is regulated by Law No. 17 of 2008, but violations of these obligations still often occur, resulting in marine accidents. This study aims to evaluate the effectiveness of criminal sanctions applied to skippers who sail without a license, as well as analyze the factors that affect the skipper's legal awareness. The legal research method used is an empirical legal approach by accumulating data through observation and interviews. The results of the study show that even though criminal sanctions have been implemented, violations still occur due to a lack of understanding of the law and economic challenges. Therefore, preventive efforts such as legal socialization and improvement of licensing services are needed to encourage compliance with regulations. This scientific paper is expected to be able to provide recommendations for policymakers in formulating more effective and sustainable law enforcement strategies in the fisheries sector.